Vapour-Deposited Cesium Lead Iodide Perovskites: Microsecond Charge Carrier Lifetimes and Enhanced Photovoltaic Performance - Hutter, Eline M. (ACS Energy Lett, 2017)
[Image: see text] Metal halide perovskites such as methylammonium lead iodide (MAPbI(3)) are highly promising materials for photovoltaics. However, the relationship between the organic nature of the cation and the optoelectronic quality remains debated. In this work, we investigate the optoelectronic properties of fully inorganic vapour-deposited and spin-coated black-phase CsPbI(3) thin films. Using the time-resolved microwave conductivity technique, we measure charge carrier mobilities up to 25 cm(2)/(V s) and impressively long charge carrier lifetimes exceeding 10 μs for vapour-deposited CsPbI(3), while the carrier lifetime reaches less than 0.2 μs in the spin-coated samples. Finally, we show that these improved lifetimes result in enhanced device performance with power conversion efficiencies close to 9%. Altogether, these results suggest that the charge carrier mobility and recombination lifetime are mainly dictated by the inorganic framework rather than the organic nature of the cation.